Natural gas dehydration using silicagel : fabrication of dehydration unit - Siti Suhaila, Mohd Rohani (2009)
The purpose of this study is to remove water content in untreated natural gas using solid desiccant dehydration unit. Dehydration of natural gas is needed to remove the water that is associated with natural gases in vapor form. The natural gas industry has recognized that dehydration is necessary to ensure smooth operation of gas transmission lines. Dehydration prevents the formation of gas hydrates and reduces corrosion. Unless gases are dehydrated, liquid water may condense in pipelines and accumulate at low points along the line and reducing its flow capacity. Several methods have been developed to dehydrate gases on an industrial scale. The three major methods of dehydration are direct cooling, adsorption, and absorption. In this experiment, the adsorption process was choosing. Silica gel was the desiccants used in adsorption processes. The desiccant dehydration is a very simple process, ideal for remote locations with limited utilities, environment benefit, easy to install and operate and it also suitable in laboratory scale. In this study, it focuses on designing, fabrication, hydrostatic test and experimental part. On the experimental part, the quality of the desiccant and the temperature is constant because it only focuses on operating pressure. At a constant temperature the water content of the gas decreases with increasing pressure, thus less water must be removed if the gas is dehydrated at a high pressure.